Personal engagement of basketball athletes: Insights from mixed methods research - Maciel, L. F.; Beirith, M. K.; Ibáñez, S. J.; Galatti, L. R.; Farias, G. O.; Folle, A. (Journal of Physical Education and Sport, 2024)
Research on sports training is carried out in numerous countries. However, the majority is carried out with athletes who have reached the elite of the sport, observing gaps in the analysis of the training process of athletes in the final phase of training and in transition to the adult categories. This study aimed to explore basketball players` perspectives on their engagement in physical and sporting activities, considering their motivation levels, weekly frequency of participation, and additional physical activities undertaken during their training. A mixed methods research (MMR) approach was employed, using a sequential explanatory strategy. First, a quantitative study was performed with Brazilian athletes aged 18 and 19 (n=141; 78.7% male, 21.3% female). Subsequently, 24 in-depth qualitative interviews were carried out. Differences between age groups were analyzed using the Kruskal-Wallis test and the association between qualitative variables was analyzed using the Chi2 test. Coding and analysis of qualitative data were guided by Thematic Analysis. The results showed that up to the age of 10, few athletes played basketball, and those who did pursued the sport for leisure. From the age of 11, most were already training systematically and at 13 they started participating in competitions. At the age of 15, the weekly training frequency increased significantly, as did the motivation to practice and the influence of school sports involvement in basketball, remaining high until the ages of 18 and 19. Following the Developmental Model of Sports Participation logic, the results obtained demonstrated that athletes have a sporting diversification until the age of 10, approximately from 11 to 14 years old they experience the specialization stage and at 15 they begin to dedicate themselves specifically to basketball. This study has the potential to significantly impact theory and practice, regarding MM research and the elements that influence athletes' personal engagement and, consequently, the youth sports system.